Rinodina evae (Physciaceae, Ascomycota), a new corticolous blastidiate species from Eastern Spain - Fos, Simón; Giralt, Mireia (Nova Hedwigia, 2009)
Rinodina evae, a new corticolous species, is described from Eastern Spain. It is mainly characterized by a blastidiate, hairy thallus, Pachysporaria-type ascospores and the lack of secondary lichen substances. Hitherto, it is only known from several cork-oak forests of Catalonia and the Valencian Community, where it always grows on virgin bark of Quercus suber. The new species is compared with Rinodina poeltiana, somewhat similar in habit, as well as with other corticolous blastidiate Rinodina species.
Keywords: Biodiversity; cork-oak forests; iberian peninsula; lichens; Rinodina; taxonomy

Rinodina evae (Physciaceae, Ascomycota), a new corticolous blastidiate species from Eastern Spain (Nova Hedwigia, 2009)
Rinodina evae, a new corticolous species, is described from Eastern Spain. It is mainly characterized by a blastidiate, hairy thallus, Pachysporaria-type ascospores and the lack of secondary lichen substances. Hitherto, it is only known from several cork-oak forests of Catalonia and the Valencian Community, where it always grows on virgin bark of Quercus suber. The new species is compared with Rinodina poeltiana, somewhat similar in habit, as well as with other corticolous blastidiate Rinodina species.